2022
DOI: 10.1111/os.13596
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties of Novel Lateral Hole Pedicle Screws and Solid Pedicle Screws: A Comparative Study in the Beagle Dogs

Abstract: Objective: Although pedicle screws are widely used to reconstruct the stability of the spine, screw loosening is a common complication after spine surgery. The main objective of this study was to investigate whether the application of the hollow lateral hole structure had the potential to improve the stability of the pedicle screw by comparing the biomechanical properties of the novel lateral hole pedicle screws (LHPSs) with those of the solid pedicle screws (SPSs) in beagle dogs. Methods:The cancellous bone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…A previous study 26 compared the biomechanical properties of hollow lateral holes and solid screws. The results of this study showed that hollow lateral hole screws had significantly better pull‐out and bending resistances than solid screws.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 26 compared the biomechanical properties of hollow lateral holes and solid screws. The results of this study showed that hollow lateral hole screws had significantly better pull‐out and bending resistances than solid screws.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, osteoporosis is a crucial risk factor of screw loosening [24] . The density of bone at the interface between the bone and screw has been found to be closely linked to the occurrence of screw loosening [3,25] .…”
Section: Discussionmentioning
confidence: 99%